2006
DOI: 10.1001/archpsyc.63.7.757
|View full text |Cite|
|
Sign up to set email alerts
|

Two-Year Randomized Controlled Trial and Follow-up of Dialectical Behavior Therapy vs Therapy by Experts for Suicidal Behaviors and Borderline Personality Disorder

Abstract: Our findings replicate those of previous studies of DBT and suggest that the effectiveness of DBT cannot reasonably be attributed to general factors associated with expert psychotherapy. Dialectical behavior therapy appears to be uniquely effective in reducing suicide attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,087
13
73

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,671 publications
(1,250 citation statements)
references
References 56 publications
58
1,087
13
73
Order By: Relevance
“…Therapies which directly target experiential avoidance, such as accep-tance and commitment therapy (ACT), or DBT (which also addresses cognitive dissonance, as noted above [80]), may be useful in augment-ing treatment for patients with PNESs [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapies which directly target experiential avoidance, such as accep-tance and commitment therapy (ACT), or DBT (which also addresses cognitive dissonance, as noted above [80]), may be useful in augment-ing treatment for patients with PNESs [87].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on implicit cognition have conceptualized such discrepancies from within a cognitive dissonance theory perspective [78], suggesting that aversive dissonance-related discomfort increases when implicit and explicit beliefs diverge [79]. The application of cognitive dissonance theory to PNESs may, therefore, suggest that nonepileptic seizures function to reduce cognitive dissonance, and targeting this dissonance (e.g., using strategies from dialectical behavior therapy (DBT; [80])), is an avenue for future research and treatment approaches in populations with PNESs.…”
Section: Experiential Avoidancementioning
confidence: 99%
“…When the completion of the study was threatened by the high rate of attrition, the researchers responded by using intensive case managers to maintain contact with clients through a community phone-mail account, and by calling client's friends, family, clergy, probation officers, and other mental health providers when contact was lost. Another example of treatment engagement is evident in Linehan's DBT (Linehan, 1993), which has been found to be an effective treatment for reducing suicide related-behavior in individuals with borderline personality disorder in multiple studies (Linehan et al, 1999;Linehan et al, 2006). In DBT, suicide-related behavior is conceptualized as maladaptive problem-solving.…”
Section: Cognitive Behavioral Therapy (Cbt) To Reduce Suicidal Behaviormentioning
confidence: 99%
“…A RCT of schema-focused therapy among patients with borderline personality disorder also reported positive outcomes with regard to the number of episodes of DSH (Giesen-Bloo et al, 2006). To date, dialectical behavioural therapy is the only CBT intervention studied in more than one RCT, and has consistently been found to reduce self-injury in (female) patients with borderline personality disorder (Linehan et al, 2006). Furthermore, a recent RCT showed that DSH patients who received CBT in addition to usual care had signifi cantly greater reductions in DSH, suicidal cognitions, symptoms of depression and anxiety and signifi cantly greater improvements in self-esteem and problem-solving ability than controls (Slee et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%